Considerações sobre a reprodução de duas espécies de raias (Myliobatiformes, Potamotrygonidae) na região do Alto Rio Paraná, Sudeste do Brasil - Garrone Neto, Domingos [UNESP] (My University, 2010)
This article presents preliminary information about the reproduction of two species of freshwater stingrays of the genus Potamotrygon, found in the Upper Parana River (Southwest Brazil), where these animals are exotic. Males of P. motoro and P. falkneri become sexually mature around 270 mm and 260 mm of disc width (DW), respectively. Females become sexually mature around 330 mm of DW in P. motoro and 325 mm in P. falkneri. In both species, females are bigger and heavier than males, reaching about 700 mm of DW and 20 kg. Copulating has not been recorded, but one courtship ritual has been observed during the dry season. Mature males present a different dentition from females and young males, which is probably related to their reproductive behavior instead of to their feeding habit. The female fertility has varied from one to three offspring. A miscarriage has been observed at different stages of embryonic development always when pregnant females were captured. In spite of the great history of anthropization of the study area, it seems that hydrological cycles are related to the reproduction of stingrays. Nevertheless, it would be necessary to conduct deeper studies to verify or not this influence.
Considerations on the reproduction of two species of stingrays (Myliobatiformes, Potamotrygonidae) in the Upper Parana River, southeastern Brazil.